Geological and oceanographic data determining the foreshore zone according to the Greek legislation - PEHLIVANOGLOU, K.G.; RAPPOU, M.; MARTSOUKOU, M. (Mediterranean Marine Science, 2006)
The available scientific field data of the marine and the coastal enviroment, (wind and wave field data, shallow area bathymetry, coastal area geomorphology and topography, etc.), in addition to deep and shallow wave prediction numerical modelling (by means of wind and bathymetry measurements), calculation of the nearshore wave height and maximum wave run up, were used to support the mapping of the innermost limit of the foreshore zone according to Greek legislation which defi nes that ‘the foreshore is the zone of land wetted by the highest however unexceptional sea wave run up’ and the Supreme Administrative Court standard case law. These methods were applied for two areas, which completely differ as regards the wind and the wave field, the geomorphological and topographical characteristics of the coastal area, suggesting different procedures for the determination of the innermost limit of the foreshore zone. The limits of the foreshore zones for both areas, resulting from the study, are compared to the limits set out by the authorised Administrative Commissions, which were published in the Official Gazette and also were applied by the local authorities for the management of the coastal area.